A Study on English Speaking Skill Development of Exchange Participant Returnee from Aiesec Global Volunteer Program of An English Student in Universitas Tanjungpura - Cornelia, Feren; Yohanes Gatot Sutapa Yuliana; Dwi Riyanti (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research was aimed to find out English speaking skill developments of exchange participant returnee from AIESEC global volunteer program and how this program can contribute in the participant’s speaking skill development in Universitas Tanjungpura Pontianak. This research used a case study research. To collect the data, the researcher used interview. The purpose of the study was to know what the developments of exchange participant returnee from AIESEC’s global volunteer program to know the contribution of AIESEC’s global volunteer program toward the student’s speaking skill development in Universitas Tanjungpura Pontianak. The researcher decided to conduct this research study into a student of English Language Education Study Program batch 2016 that have been returned from the AIESEC global volunteer program. The results revealed that the participant has some developments in English speaking skill such as pronunciation, fluency and vocabulary. In conclusion, this research study is produced positive finding regarding to the volunteer program that have been followed by the participant towards his English speaking skill.